Evaluation of interaction among arsenic and Brevibacterium sp. strain CS2 and its proteins profiling - Shahid Sher; Sajjad Ullah; Dilara Abbas Bukhari; Syed Zajif Hussain; Abdul Rehman (Journal of Hazardous Materials Letters)
In this study, Brevibacterium sp. strain CS2 was used to evaluate the mechanisms of arsenic interaction with the bacterium and its enzymatic and protein profiling under arsenic stress. The bacterium was capable to resist the arsenate 280 mM and arsenite 40 mM as per MIC. The whole genome, available on NCBI, was analyzed for genes associated with arsenic, which confirmed the genes for both arsenic oxidation (aioB) and arsenic reduction arsR, arsC, ACR3, and arsB. The sharpening and shifting of FTIR spectra in the ranges of 3278–2851 cm−1 are due to hydroxyl and amide stretching. SEM analysis showed no significant changes in morphology in arsenic stress while EDX analysis proved the arsenite interaction by showing arsenic peaks in the graph. Both glutathione and non-protein thiol showed different responses in the absence and presence of arsenic stress. Protein bands such as 25, 30, 32, 37, 42, 48, and 100 kDa were expressed more in arsenic-treated samples as compared to the control one. The presence of arsenic oxidizing genes, the ability to resist arsenic, and the varied response of enzymes and proteins in arsenic stress make the bacterium a suitable agent for arsenic eradication from contaminated sites.